2011
DOI: 10.1089/neu.2010.1493
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and Functional MRI in Post-Acute Mild Traumatic Brain Injury

Abstract: Symptoms persisting beyond the acute phase (>2 months) after a mild traumatic brain injury (MTBI) are often reported, but their origin remains controversial. Some investigators evoke dysfunctional cerebral mechanisms, while others ascribe them to the psychological consequences of the injury. We address this controversy by exploring possible cerebral dysfunction with functional magnetic resonance imaging (fMRI) and event-related potentials (ERP) in a group of patients during the post-acute phase. Fourteen MTBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 38 publications
5
61
0
Order By: Relevance
“…None of the participants had any injury visible in conventional MRI. In accordance with previous DTI, functional MRI, and positron emission tomography studies, [5][6][7][8][9][10][11] we expected to see mTBI related changes in nTMS-EEG responses of the frontal areas, especially with nTMS of the DLPFC. We also expected to find more pronounced changes in the symptomatic participants compared with those who had recovered.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…None of the participants had any injury visible in conventional MRI. In accordance with previous DTI, functional MRI, and positron emission tomography studies, [5][6][7][8][9][10][11] we expected to see mTBI related changes in nTMS-EEG responses of the frontal areas, especially with nTMS of the DLPFC. We also expected to find more pronounced changes in the symptomatic participants compared with those who had recovered.…”
Section: Introductionsupporting
confidence: 89%
“…[1][2][3][4] DTI has shown altered fractional anisotropy and diffusion after mTBI in the corpus callosum, in the dorsolateral prefrontal cortex (DLPFC) region, and in frontal white matter regions. [5][6][7][8][9] Decreased resting state activity 10 and activation related blood flow response 11 have been observed in prefrontal areas in mTBI, correlating with symptom severity. These results suggest that structural damage may be present in mTBI and may explain the persistent symptoms experienced by some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the MTBI group, 14 patients had been included in a previous ERP and fMRI study in our laboratory. 23 The MTBI group was compared with 40 control volunteers who were their equivalent for age and sex. No control participants had a diagnosis or history of neurological and/or psychiatric conditions (including previous TBI and substance abuse) and no one used drugs known to affect cognition.…”
Section: Patient Populationmentioning
confidence: 99%
“…In a recent study, preliminary data on 14 patients with MTBI or concussion showed that the frontal N350 ERP wave associated with WM was abnormal when compared with control volunteers. 23 This anomaly was concurrently associated with reduced fMRI activation in the mid-DLPFC during the performance of the same externally ordered WM task. These results need to be confirmed in a larger sample of patients with different types of injury, for example motor vehicle accident and sports concussion.…”
mentioning
confidence: 98%
See 1 more Smart Citation